Mental Health Services for Syrian Refugees in Lebanon: Perceptions and Experiences of Professionals and Refugees. (May 2020) - Kerbage, Hala; Marranconi, Filippo; Chamoun, Yara; Brunet, Alain; Richa, Sami; Zaman, Shahaduz
We applied semi-structured and in-depth interviews to explore the perceptions and experiences of 60 practitioners/policymakers and 25 Syrian participants involved in mental health services for refugees in Lebanon. Refugees were found to view their distress as a normal shared reaction to adversity while professionals perceived it as symptomatic of mental illness. Practitioners viewed Syrian culture as an obstacle to providing care and prioritized educating refugees about mental health conditions. Policymakers invoked the state of crisis to justify short-term interventions, while Syrian refugees requested community interventions and considered resettlement in a third country the only solution to their adverse living conditions. The therapeutic relationship seems threatened by mistrust, since refugees change their narratives as an adaptive mechanism in response to the humanitarian system, which professionals consider manipulative. We discuss the implications of our findings for mental health practice in humanitarian settings.